Influence of Anxiety Disorder on Emotional and Social Adjustment of Internally Displaced Persons in Durumi-1 Camp Abuja Nigeria - Moses, Solomon (International Journal of Human Kinetics, Health and Education, 2023)
This study investigated the influence of Anxiety on Emotional and Social Adjustment of Internally Displaced Persons in Durumi Camp Abuja Nigeria. Ex-post Facto research design was used for the study. Population of the study comprises of male and female late adolescent and adult IDPs. 380 IDPs were sampled out of 1,260 IDPs in Durumi Camp using simple random sampling technique. The two Instruments used for the study are Harvard Trauma questionnaire (HTQ) with focus on anxiety symptoms and Psychological Adjustment Scale (PAS) with emotional and social adjustment as sub scales. Two research questions were formulated with their corresponding null hypotheses. Pearson Product Moment Correlation was used to test the hypotheses at 0.05 level of significant. The results show that anxiety has a significant negative relationship on emotional adjustment of IDPs (r = - 0.758, p = 0.004). Anxiety has a significant negative relationship on social adjustment of IDPs (r = - 0.744, p = 0.001). Based on the findings of this study, it was recommended that the affected IDPs should be given immediate attention in form of psychological treatment or intervention so as to live a meaningful life.